(untitled) (Eurasian Research Bulletin, 2023)
The phrase "technology-enhanced learning" is frequently used when talking about the position and use of technology in education. Yet, there are still a lot of pedagogical holes that need to be filled in order to lift the fascination that surrounds technology-enhanced learning and guarantee that its usage is deliberate. The several potential uses of the technology should be considered while planning. The pedagogical factors for a learning process aided by technology are outlined in this research. In fact, it is frequently believed that just integrating technology into the classroom will suffice, without particularly reformatting the pedagogical model. The possible objectives of utilizing technology in the educational process are examined in the study. It also examines the pedagogical elements—learning motivation, cognitive growth, cognitive load, and knowledge development—that contribute to the effectiveness of technology-enhanced learning